UPAYA GURU MEMBERIKAN BIMBINGAN SOSIAL PRIBADI PADA SISWA SEKOLAH DASAR NEGERI 1 SAREE KECAMATAN LEMBAH SEULAWAH KABUPATEN ACEH BESAR - Ulya, Rahmatun; Hasmiana, Hasmiana; M. Husin, M. Husen (Universitas Syiah Kuala, 2019)
Personal social guidance is given to individuals, in order to be able to face and solve their personal social problems independently. It is known from the behavior of students who make noise in class disrupting their students who are studying in class. This researcher aims to determine the motivation of teachers in providing spiritual guidance to students of SD 1 Saree, Seulawah Valley, Aceh Besar District. to describe teacher barriers in giving spiritual guidance to students of SD 1 Saree, Lembah Seulawah District, Aceh Besar District. The subjects in this study were 6 homerooms from class I to class VI. Data collection techniques are using observation and interviews. The data were analyzed using data reduction, data presentation, conclusion. The results showed that personal social guidance for students at Saree 1 Elementary School in Lembah Seulawah Subdistrict, Aceh Besar Regency was done by (1) Teachers preparing to plan coaching carried out in coaching for students who experience problems in personal social development. (2) The teacher also fosters students by giving advice and demonstrating exemplary behavior to students. (3) The next step undertaken by the teacher is to give a warning if the coaching process cannot run well. (4) The final step taken by the teacher in guiding students' personal social skills by providing motivation and assistance. The obstacle faced by teachers in providing personal social guidance for students is the limited time available.